High prevalence of clustered tuberculosis cases in Peruvian migrants in Florence, Italy - Lorenzo Zammarchi; Enrico Tortoli; Emanuele Borroni; Filippo Bartalesi; Marianne Strohmeyer; Simonetta Baretti; Maria Tullia Simonetti; Carola Liendo; Maria Grazia Santini; Gian Maria Rossolini; Eduardo Gotuzzo; Alessandro Bartoloni (MDPI AG, 2014)
Tuberculosis is a leading cause of morbidity for Peruvian migrants in Florence, Italy, where they account for about 20% of yearly diagnosed cases. A retrospective study on cases notified in Peruvian residents in Florence in the period 2001-2010 was carried out and available Mycobacterium tuberculosis strains were genotyped (MIRU-VNTR-24 and Spoligotyping). One hundred thirty eight cases were retrieved. Genotyping performed in 87 strains revealed that 39 (44.8%) belonged to 12 clusters. Assuming that in each cluster the transmission of tuberculosis from the index case took place in Florence, a large proportion of cases could be preventable by improving early diagnosis of contagious cases and contact tracing.